Quantum Teaching Learning (QTL) Learning Model Innovation in PAI - Agung Cahya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic Religious Education (PAI) in the modern era faces challenges such as declining learning motivation and the perception that religious instruction lacks relevance amidst the wave of digitalization. This study examines the innovation of the Quantum Teaching and Learning (QTL) model as a strategic solution to create an active, meaningful, and enjoyable PAI learning process. The study aims to analyze the fundamental concepts, principles, and application of QTL within the context of PAI, as well as to identify its innovations and impact on student learning outcomes. Employing a literature review and conceptual analysis approach, the study explores the QTL framework—grounded in the principle of